UJI VALIDITAS DAN RELIABILITAS TERHADAP BUTIR ITEM MINDFULNESS FOKUS ASPEK KOGNITIF PADA REMAJA DENGAN MASALAH MENTAL EMOSIONAL DI KLINIK TALENTA CENTER BEKASI - Dinda Amalia Suryadi (2022)
Mental emotional problems are a conditions where an individual is experiencing an emotional change and if it continues it can be a change in the development of pathological conditions so that it is necessary anticipatory to maintain mental health. One of the interventions that can be done to overcome these problems is by doing mindfulness therapy. This therapy can be done at the Therapy Center & Special Talent School, which is an educational institution for children with special needs such as autism, ADHD, depression, anxiety, OCD and so on. This study aims to develop a research instrument in the form of a cognitive aspect of mindfulness questionnaire with the stages of testing the validity and reliability of the questionnaire. Data were collected through a total sampling of 30 patients who met the inclusion criteria at the Talenta Center Clinic. The results of the validity test obtained are 17 valid questionnaire items with a value of r count > r table (0.3610) and the other 5 items are invalid with a value of r count < r table (0.3610) and the results of the reliability test on the 17 items. shows reliable where the value of Cronbach alpha coefficient is > 0,6. The cognitive aspect of the mindfulness questionnaire as a research instrument has gone through the process of preparing and testing the terms and is suitable for use in further research.